Copper-Catalyzed Intermolecular Thioamination of Maleimides with Thiols and Formamides: A One-Step Construction of 3-Amino-4-thiomaleimides Using Formamides as Nitrogen Sources - Yang, Zhen-Hua; Zhu, Jia-Nan; Jin, Ze-Hui; Zheng, Jian; Zhao, Sheng-Yin (Synthesis, 2018)
A highly efficient copper-catalyzed intermolecular C(sp2)–H thioamination of maleimides with thiols and formamides in the presence of fluoroboric acid is reported using various readily available formamides as nitrogen sources and solvents. A diverse range of 3-amino-4-thiomaleimides is obtained with good yields under mild conditions, involving C–N and C–S bond formation. This methodology enriches current C–N and C–S bond formation chemistry and features operational simplicity and excellent functional-group tolerance.
Keywords: copper catalysis; thioamination; maleimides; thiols; formamides